The complete learning disabilities handbook : ready-to-use strategies & activities for teaching students with learning disabilities. - Harwell, Joan M.; Jackson, Rebecca Williams (San Francisco, Calif. : Jossey-Bass, 2008)
A comprehensive source of information, strategies, and activities for working with learning disabled students.
Previous ed. published: Paramus, N.J. : Center for Applied Research in Education, 2001.
Includes bibliographic references (p. 365-375) and index.
Keywords: Learning disabled children; Special education; Learning disabilities; Remedial teaching; Learning disabled youth; Didaktik; Lernbehinderung; Schüler.